Development of an automated assessment technology for detecting damage in body armour. (October 2020) - Marks, Ryan; Grigg, Stephen; Crivelli, Davide; Pearson, Matthew; Eaton, Mark; Llŷr, Iestyn; McHugh, Martin; Wotherspoon, Tracy; Pullin, Rhys
Hard ballistic body armour plates are designed to withstand the impact of a bullet and protect the wearer, if this happens the armour is clearly damaged and so is retired from service. Mishandling, however, such as dropping the armour, may cause minor and difficult to detect damage which compromises the effectiveness of the plate. Current methods of inspection involve shipping the plates to a central location, performing a thorough inspection and returning them to service if uncompromised; this is costly and requires redundancy of equipment for when not in service. Acousto-Ultrasonics is a method of structural health monitoring in which ultrasonic waves are excited in a structure by a transducer and receivers record the response, any deviation from a baseline measurement give an indication of damage within the structure. Within this paper the development and testing of a novel handheld prototype device is presented, which gives a simple yes/no answer to if there is damage on the plate. This inspection is quick and easy to perform by unskilled personnel. Low profile sensors have been utilised combined with a novel flexible circuitry with built in memory, which does not compromise the effectiveness of the armour.